PEMBINAAN REHABILITASI SOSIAL DI KOTA PEKANBARU TAHUN 2016 - Dewi Sebrina. L; Wan Asrida (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Development of Social Rehabilitation in Pekanbaru City for neglected adolescents carried out by the Social Service and Funeral City of Pekanbaru. This is the implementation of Social Rehabilitation by providing guidance and training to Juvenile Delinquency. Where coaching and training activities include religious guidance, providing skills training. The implementation of fostering social rehabilitation carried out by the Social Service and Funeral of Pekanbaru City includes Giving direction, Giving guidance, Supervising, Providing education and training.This study aims to determine the Development of Social Rehabilitation and Cemeteries in Pekanbaru City in 2016 and determine the factors of obstacles in the implementation of Social Rehabilitation and Funerals in Pekanbaru City in 2016. The research method used is using qualitative methods. This method aims to get a true picture of the development of social rehabilitation in the city of Pekanbaru in 2016. The method used in interviews and documentation of the data obtained is analyzed carefully.The results of research on the implementation of Social Rehabilitation in Pekanbaru City in 2016 against juvenile delinquency have not been carried out to the maximum through religious coaching activities and skills training. training coaching activities that have not yet provided the attainment of adolescent abilities in the knowledge of the given training field.The conclusion that the Development of Social Rehabilitation in Pekanbaru City against juvenile delinquency carried out by the Social Service and Funeral of the City of Pekanbaru is not well implemented. Suggestions in this study are the need for the provision of infrastructure facilities in support of coaching and training activities, the need to increase the number of employees in conducting coaching and training and to increase the time of coaching and training activities. Keywords: Coaching, Rehabilitation, Juvenile Delinquency